Characterization of Streptomyces spp. Producing Indole-3-acetic acid as Biostimulant Agent - Charlie Ester de Fretes; Langkah Sembiring; Yekti Asih Purwestri (Universitas Gadjah Mada, 2013)
Twenty six isolates of Streptomyces spp. obtained from Cyperus rotundus L. rhizosphere were tested forability to produce indole-3-acetic acid (IAA) in yeast malt extract (YM) medium containing 2 mg/mL tryptophan.Screening of the isolates for ability to produce IAA was carried out by adding Salkowski reagent in bacteriaculture and was measured quantitatively by spectrophotometer at λ 530 nm. Thin Layer Chromatography (TLC)method was used to determine IAA. To ensure the IAA production in Streptomyces isolates, gene involved inIAA biosynthesis was detected by amplifying Tryptophan Monooxigenase (iaaM) gene. The study of the effectof tryptophan on the production of IAA was measured at different concentrations of tryptophan (0, 1, 2, 3,4, 5 mg/mL) in the bacterial culture. The result showed that there were two Streptomyces spp. isolates whichcould produce IAA, namely the isolates of Streptomyces sp. MS1 (125.48 μg/mL) and Streptomyces sp. BR27(104.13 μg/mL). The TLC result showed that the compound in both isolates was identifi ed to be IAA. Theamplifi cation results showed that iaaM gene was detected in both isolates. This results indicated that the IAMpathway is predicted involved in the biosynthesis of IAA in the selected isolates. Both of the isolates were ableto produce IAA after 24 h incubation and the highest production was at 120 h incubation with the concentrationof tryptophan was 2 mg/mL dan 1 mg/mL, respectively. Therefore, it is concluded that Streptomyces spp.isolates are able to produce IAA and potentially to be utilized as biostimulat agent. Keywords: Streptomyces spp., indole-3-acetic acid (IAA), indole-3-acetamide (IAM), Tryptophan Monooxigenasegene (iaaM)